2011
DOI: 10.1016/j.pmrj.2011.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Concepts in the Treatment of Myofascial Pain: A Review of Medications, Modalities, and Needle‐based Interventions

Abstract: Significant developments and changes in the use of interventions and treatments for the management of myofascial pain syndrome have occurred in the past 10 years. These emerging concepts have changed the approach for clinicians who manage these pain disorders. However, wide variations in practice patterns prevail, and no clear consensus exists regarding when and how to use these interventions; in addition, awareness of the evidence basis behind their use is limited. This review examines the most recent advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 128 publications
1
40
0
2
Order By: Relevance
“…Overall, our findings in this study, like previous studies, support that MPS still lacks a clear treatment frame 4 and its management should be based on a multimodal approach. 5 …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Overall, our findings in this study, like previous studies, support that MPS still lacks a clear treatment frame 4 and its management should be based on a multimodal approach. 5 …”
Section: Discussionsupporting
confidence: 87%
“…In previous studies also, LLLT was reported to be effective in the treatment of MPS as an adjunctive treatment. 4,5 In Gur et al study, the use of LLLT was effective in treating neck MPS compared to placebo. 10 Carrasco et al also reported that LLLT was effective in pain reduction of patients with MPS.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Dentro de los procedimientos invasivos se incluyen tratamientos como punción seca de los puntos gatillo con aguja (7,10,11), la infiltración con anestésicos locales (12) y esteroides (13) en los puntos gatillo. De igual forma se ha utilizado la toxina botulínica tipo A (TXB A) para la infiltración de puntos gatillo (14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionunclassified